Tranexamic Acid vs Adrenaline for Controlling Iatrogenic Bleeding During Flexible Bronchoscopy: A Double-Blind Randomized Controlled Trial - Badovinac, Sonja; Glodić, Goran; Sabol, Ivan; Džubur, Feđa; Makek, Mateja Janković; Baričević, Denis; Koršić, Marta; Popović, Filip; Srdić, Dražena; Samaržija, Miroslav (Chest, 2023)
The most commonly used topical hemostatic agents during flexible bronchoscopy (FB) are cold saline and adrenaline. Data on use of other agents such as tranexamic acid (TXA) for this purpose are limited. Is TXA effective and safe in controlling iatrogenic bleeding during FB compared with adrenaline? We conducted a cluster-randomized, double-blind, single-center trial in a tertiary teaching hospital. Patients were randomized in weekly clusters to receive up to three applications of TXA (100 mg, 2 mL) or adrenaline (0.2 mg, 2 mL, 1:10000) after hemostasis failure after three applications of cold saline (4 ° C, 5 mL). Crossover was allowed (for up to three further applications) before proceeding with other interventions. Bleeding severity was graded by the bronchoscopist using a visual analog scale (VAS; 1 = very mild, 10 = severe). A total of 2,033 FBs were performed and 130 patients were randomized successfully to adrenaline (n = 65) or TXA (n = 65), whereas 12 patients had to be excluded for protocol violations (two patients from the adrenaline arm and 10 patients from TXA arm). Bleeding was stopped in 83.1% of patients (54/65) in both groups (P = 1). The severity of bleeding and number of applications needed for bleeding control were similar in both groups (adrenaline: mean VAS score, 4.9 ± 1.3 [n = 1.8 ± 0.8]; TXA: mean VAS score, 5.3 ± 1.4 [n = 1.8 ± 0.8]). Both adrenaline and TXA were more successful in controlling moderate bleeding (86.7% and 88.7%, respectively) than severe bleeding (40% and 58.3%, respectively; P = .008 and P = .012, respectively) and required more applications for severe bleeding (3.0 ± 0 and 2.4 ± 0.5, respectively) than moderate bleeding (1.7 ± 0.8 and 1.7 ± 0.8, respectively) control (P = .006 and P = .002, respectively). We observed no drug-related adverse events in either group. We found no significant difference between adrenaline and TXA for controlling noncatastrophic iatrogenic endobronchial bleeding after cold saline failure, adding to the body of evidence that TXA can be used safely and effectively during FB. ClinicalTrials.gov; No.: NCT04771923; URL: www. gov.